The Impact of Entrepreneurial Attitudes - Puch Coronado, Mariella Elizabeth (2023)
Entrepreneurship’s importance is growing due to its direct impact on reducing labor and economic disparities. Therefore, it is essential to develop and strengthen the different elements that foster it. Attitude is one of these fundamental elements and is related to those who plan to start a business or take advantage of new business opportunities. Thus, based on the scientific contributions that have addressed the subject and the theoretical arguments analyzed, it is clear that the entrepreneurial attitude becomes one of the personal competencies that drive the decisions that are made in the entrepreneurial journey, leading to the recognition of an individual's entrepreneurial potential. This article presents studies on attitude and the entrepreneurial attitude construct, including models that propose key factors for generating entrepreneurship, regardless of the business unit’s type and size. The article also emphasizes the importance of entrepreneurial training to develop not only technical skills but also the personal skills of a venture’s promoter, allowing to face the challenges of the entrepreneurial journey.